Dialogue as a constituent experience in the initial training of the Mathematics teacher (Práxis Educativa, 2021)
Based on the Freirean premises, this work makes explicit the dialogical relevance in initial teacher training, being the result of an experience developed in the context of the Supervised Internship with 14 undergraduate students of the Mathematics course of the University for International Integration of the Afro-Brazilian Lusophony (UNILAB). In this investigation, the dialogue assumes the condition of theoretical category, and the methodological assumptions are based on the qualitative approach. The reflections coming from this dialogic moment highlight the importance of the contact of teachers in training with more experienced professionals and strengthen the Supervised Internship as an opportunity to contact diverse practices and knowledge, beyond the knowledge of the complexity that permeates the school.Keywords: Freirean dialog. Supervised Internship. Initial training of the Mathematics teacher.